Pembuatan Karbon Aktif Melalui Karbonisasi Batang Kelapa Sawit - Delviana Dwi Jaya; Miftahul Khair (Departemen Kimia FMIPA UNP, 2020)
Providing low cost activated carbon from oil palm trunk waste is beneficial to compete with low-cost non-halal sources. This research aims to produce low cost and easy preparation of activated carbon from oil palm trunks with employ carbonization process only. With an optimum carbonization temperature of 250 oC for 150 minutes of heating time, the results of the carbonization of oil palm trunk could fulfill the proximate analysis (yield, air content, ash content, carbon content, and iodine numbers) required by Indonesian National Standard SNI 06-3730-1995 for activated carbon. The proximate analysis obtained is a yield of 50.95%, the air content of 5.71%, ash content 6.57%, the carbon content of 18.55%, carbon content increased of 74.88%, and number rs iodine of 401,6537 mg/g.